2002
DOI: 10.1017/s0952836902000602
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization, ranging behaviour and habitat use of the kodkod (Oncifelis guigna) in southern Chile

Abstract: The kodkod Oncifelis guigna has one of the smallest distributions of wild felids, being geographically restricted to a narrow strip within Chile and Argentina. An investigation of population demography and habitat selection was carried out using trapping and radio-telemetry techniques in transitional Valdivian forest at two sites in southern Chile. The mean home-range size was estimated at 269 ha with considerable overlap of ranges and core areas giving a density of combined adults and sub-adults of 0.97/km 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 14 publications
5
57
1
3
Order By: Relevance
“…Our results suggest that guiñas are mostly nocturnal, similarly to other small neotropical felids (e.g., Leopardus geoffroyi, L. colocolo) (Cuéllar et al 2006;Lucherini et al 2009), and partially differ with previous studies from radio-collared guiñas in southern localities (i.e., suggesting asymmetrical and nocturnal/crepuscular daily activity patterns - Dunstone et al 2002a;Sanderson et al 2002). Prior fi ndings have suggested that guiña active behaviour may correspond with peak activity of small mammals (Sanderson et al 2002), which are the species' main prey items (up to 82%, Dunstone et al 2002b).…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…Our results suggest that guiñas are mostly nocturnal, similarly to other small neotropical felids (e.g., Leopardus geoffroyi, L. colocolo) (Cuéllar et al 2006;Lucherini et al 2009), and partially differ with previous studies from radio-collared guiñas in southern localities (i.e., suggesting asymmetrical and nocturnal/crepuscular daily activity patterns - Dunstone et al 2002a;Sanderson et al 2002). Prior fi ndings have suggested that guiña active behaviour may correspond with peak activity of small mammals (Sanderson et al 2002), which are the species' main prey items (up to 82%, Dunstone et al 2002b).…”
contrasting
confidence: 78%
“…Guiñas occur in both spotted and melanistic coat colour morphs ). They have been described as nocturnal/ crepuscular (Dunstone et al 2002a;Sanderson et al 2002;Delibes-Mateos et al 2014), inhabiting continuous and fragmented forests (Gálvez et al 2013). However, there is still much unknown about the behavioural and morphological patterns displayed by the species, since only isolated records exist (e.g., Altamirano et al 2013).…”
mentioning
confidence: 99%
“…This habitat was used as a proxy to represent the river otter primary habitat (Sepúlveda et al, 2007); 2) Forest Foray: defined as a foray with dog locations >50 m inside of a continuous native forest patch . This is the primary habitat for pudu (Silva-Rodríguez and Sieving, 2012), guigna (Dunstone et al, 2002) and Darwin's fox (Jiménez, 2007); 3) Reserve Foray: defined as forays with dog locations within the limits of the VCR; 4) Park Foray: defined as a foray with dog locations within the limits of the ACNP. All remaining forays were classified as confined to human dominated landscapes.…”
Section: Habitat Classification and Analysis Of Dog Habitat Use And Fmentioning
confidence: 99%
“…Precipitation during the coldest quarter negatively influenced the Pampas cat, but was not important for the Andean cat's distribution. In high altitudes, this variable could be related to snow, which naturally reduces the distributions of other small high altitude cat species (Dunstone et al, 2002). This underscores the idea that the Andean cat is adapted to cold, high altitude or arid environments, which gives it a competitive edge over the Pampas cat (Marino et al, 2011), and suggests it is more stress tolerant.…”
Section: Introductionmentioning
confidence: 90%